2018
DOI: 10.1016/j.jtcvs.2017.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of chordal replacement versus leaflet resection for posterior mitral leaflet prolapse

Abstract: Chordal replacement may be associated with greater freedom from reoperation and may lead to improved postoperative left ventricular function compared with leaflet resection. However, these conclusions are supported primarily by data from unadjusted observational studies, and high-quality RCTs of chordal replacement versus leaflet resection are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 47 publications
6
53
1
2
Order By: Relevance
“…Die operative Mitralklappenrekonstruktion ist die Therapie der Wahl bei der MI, da sie dem Mitralklappenersatz hinsichtlich der perioperativen Letalität und der Langzeitergebnisse überlegen ist [45]. Im Grundsatz werden Mitralklappenpathologien heute zunehmend in minimalinvasiver Technik durchgeführt, derzeit in über 60 (von insgesamt 80) Zentren, mit einem Rekonstruktionsanteil von 40-70 %.…”
Section: Minimalinvasive Mitralklappenchirurgieunclassified
See 1 more Smart Citation
“…Die operative Mitralklappenrekonstruktion ist die Therapie der Wahl bei der MI, da sie dem Mitralklappenersatz hinsichtlich der perioperativen Letalität und der Langzeitergebnisse überlegen ist [45]. Im Grundsatz werden Mitralklappenpathologien heute zunehmend in minimalinvasiver Technik durchgeführt, derzeit in über 60 (von insgesamt 80) Zentren, mit einem Rekonstruktionsanteil von 40-70 %.…”
Section: Minimalinvasive Mitralklappenchirurgieunclassified
“…Eigene Analysen aus unserem Zentrum zeigen eine Häufigkeit von 19,9 % sowie in 1,9 % die Notwendigkeit eines extrakorporalen Lungenunterstützungssystems (▶ Abb. 6)[45].…”
unclassified
“…Grade 4 had complex MAC that may require some resection and annular reconstruction. [21][22][23][24] In our patient, prolapse of anterior leaflet is seen, with grade 3 disease, so surgery is more complex and requires intense surgical expertise. Generally, to correct AML prolapse caused by a ruptured or elongated chord, surgeon will create new Gore-Tex chords.…”
Section: Managementmentioning
confidence: 84%
“…5 We are thus in the presence of 2 very efficient alternative techniques that, however, have never been appropriately compared. It is in this milieu that Mazine and colleagues 6 from Toronto have performed a review and meta-analysis of chordal replacement versus leaflet resection for posterior leaflet prolapse, published in this edition of our Journal. In this study, Mazine and colleagues 6 found that ''leaflet resection and chordal replacement are associated with similar survival and freedom from recurrent MR.…”
mentioning
confidence: 99%
“…It is in this milieu that Mazine and colleagues 6 from Toronto have performed a review and meta-analysis of chordal replacement versus leaflet resection for posterior leaflet prolapse, published in this edition of our Journal. In this study, Mazine and colleagues 6 found that ''leaflet resection and chordal replacement are associated with similar survival and freedom from recurrent MR. However, chordal replacement may be associated with greater freedom from reoperation and improved post-operative left ventricular function.…”
mentioning
confidence: 99%